Safety for Bisimulation in General Modal Logic - Hollenberg, Marco (Proceedings of the Amsterdam Colloquium, 1995)
We define a natural generalization of the notions of invariance and safety for bisimulation, and characterise the resulting notion of (n,m)-safety for bisimulation.